Cyberdakwah sebagai Media Alternatif Dakwah - Saefulloh, Aris (ISLAMICA: Jurnal Studi Keislaman, 2012)
The history of Muslims in different part of the world has shown that the religion of Islam is disseminated through various form of dakwah ranging from music, rites, and even dance. The medium of dakwah has always changed depending on the nature and character of the society in which Islam is propagated. In Indonesia for example, the Javanese music called Gamelan was used by the Nine-saints to carry out their dakwah activities. This paper tries to discuss this. It is aimed at answering the question of what is the extent to which the medium of dakwah is being used in a particular propagation activity, and what would be the implication on the dissemination of Islam in using this medium. The paper is particularly interested in investigating what it calls the cyberdakwah, namely dakwah by means of modern technology such as the internet and the like. It asks, what are the positive and negative implications of this way of dakwah for Islam and community at large? As the paper tries to come up with the answer for the question, it keeps in mind the fact that the cyberdakwah reflects the adaptive ability of the Muslims in carrying out their dakwah activities.